CYBERBULLYING AS A NEW FORM OF DANGER OF THE PSYCHOLOGICAL HEALTH OF A TEENAGER’S PERSONALITY - E. Bengina; S. Grishaeva (Вестник университета)
The problem of psychological violence in the Internet environment is raised. The reasons, types and participants of cyberbullying are described. Much attention to the mental implications of cyberbullying for all participants of interaction is given. The results of cyberbullying influence on social life and emotional condition of teenagers are presented on the basis of materials of domestic and foreign researches. Practical recommendations are examined. It is shown that there is a need for adoption of new preventive measures in connection with the rapid development and expansion of cyberbullying’s forms.